Development Strategy And Marketing System Of Maxim Kelurahan Tanah Patah Kota Bengkulu, Bengkulu Province - Meldi putra, Edo; Fariadi, Herri (Jurnal Pengabdian Mandiri, 2024)
This Thematic Community Service Program (KKN) aims to find out how the marketing communication strategy carried out by Maxim company in increasing Competitive Advantage in Bengkulu City. Maxim continues to develop and improve the quality of its products by maintaining the comfort of customers and drivers. Product Innovation, that Maxim has launched several product innovations that can support and assist application users in carrying out their daily activities. Time to Market, in conducting promotional strategies Maxim has carried out marketing promotions both offline and online. So that the output that you want to produce from this activity is a scientific article in the Journal of Community Service, a video of activities published on GoogleDrive and a Final Report in the form of a Report on the Results of the Implementation of Thematic KKN UNIVED Bengkulu Period 1. The methods used in Thematic KKN are participation, observation, interview, literature study and documentation.